Effectiveness of Hybrid Digital Learning for Hypertension Self-Management Education among Hypertensive Patients - Prima Trisna Aji; Marta Tania Gabriel Ching Cing; Elinda Rizkasari (PT. Pusmedia Group Indonesia, 2026)
Hypertension remains a major global health problem associated with poor medication adherence, inadequate self-management behavior, and uncontrolled blood pressure among patients in primary healthcare settings. This study aimed to analyze the effectiveness of Hybrid Digital Learning for Hypertension Self-Management Education in improving medication adherence and blood pressure control among hypertensive patients. This study employed a quasi-experimental pretest-posttest control group design conducted at Klinik Pratama Jatipuro Muhammadiyah Karanganyar, Central Java, Indonesia, from January to March 2026. A total of 62 participants were recruited using purposive sampling and equally divided into intervention and control groups. The intervention group received hybrid digital learning interventions consisting of face-to-face educational sessions, digital pocketbook-based learning media, and weekly monitoring for eight weeks, while the control group received standard educational services. Medication adherence was measured using the Morisky Medication Adherence Scale (MMAS-8), while blood pressure was assessed using a calibrated digital sphygmomanometer. Data were analyzed using SPSS version 26 using descriptive and inferential statistical tests. The findings demonstrated significant improvements in medication adherence scores from 5.21 ± 1.12 to 7.43 ± 0.88, reductions in systolic blood pressure from 154.61 ± 10.43 mmHg to 132.48 ± 8.71 mmHg, and reductions in diastolic blood pressure from 96.32 ± 7.14 mmHg to 84.51 ± 6.27 mmHg among participants receiving the hybrid digital learning intervention (p < 0.001). The study concludes that Hybrid Digital Learning for Hypertension Self-Management Education is effective in improving medication adherence and blood pressure control among hypertensive patients. The findings support the integration of hybrid digital learning models into primary healthcare education programs to strengthen long-term hypertension self-management and technology-assisted patient education.